Mechanical Design Of A Truck-Mounted Scatterometer Platform - Abd. Aziz, Abd. Halim (2008)
In this project, a truck-mounted scatterometer platform will be designed and developed. The scope of work includes, (i) design and selection of a suitable elevating mechanism and ensure wind induced vibration does not cause system instibility, (ii) design and selection of a suitable mobile platform and ensure compatibility with the elevating mechanism, (iii) design and development of an antenna mounting system and (iv) design and selection of work cabin an other ancillary equipment such as power generator, air-conditioning units and exhaust fan.